Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa Sekolah Dasar Melalui Pembelajaran Berbasis Masalah - Sukriadi Hasibuan; Seri Asmaidah; Agus Saleh (Institut Pendidikan Tapanuli Selatan, 2018)
The purpose of this research is to see how far the increase in mathematical creative thinking abilities of students who are given problem-based learning models with ordinary learning models. This study was conducted in class V SD Negeri 200201 Ujung Padang in Padangsidimpuan City in the second semester with a total sample of 50 students divided into experimental class and control class with a research design using Pretest-Postes Control Group Design. Based on the results of the study of the average normalized gain through mathematical creative thinking abilities of students with high, medium, and low ability obtained a score of 0.45 higher than ordinary learning with an average of 0.21. The results of the data analysis showed that the improvement of students' mathematical creative thinking skills using problem-based learning was better than students who were given ordinary learning. From the results of the study it can be concluded that problem-based learning is one alternative to improve students' creative thinking skills, find new ideas, think flexibly so that they are more flexible and detailed.